A one-dimensional tearing mode equation for pedestal stability studies in tokamaks. (14th June 2018) - Connor, J. W.; Hastie, R. J.; Marchetto, C.; Roach, C. M.
Abstract : Starting from expressions in Connor et al. ( Phys. Fluids, vol. 31, 1988, p. 577), we derive a one-dimensional tearing equation similar to the approximate equation obtained by Hegna & Callen ( Phys. Plasmas, vol. 1, 1994, p. 2308) and Nishimura et al. ( Phys. Plasmas, vol. 5, 1998, p. 4292), but for more realistic toroidal equilibria. The intention is to use this approximation to explore the role of steep profiles, bootstrap currents and strong shaping in the vicinity of a separatrix, on the stability of tearing modes which are resonant in the H-mode pedestal region of finite aspect ratio, shaped cross-section tokamaks, e.g. the Joint European Torus (JET). We discuss how this one-dimensional model for tearing modes, which assumes a single poloidal harmonic for the perturbed poloidal flux, compares with a model that includes poloidal coupling Fitzpatrick et al. ( Nucl. Fusion, vol. 33, 1993, p. 1533).